1988
DOI: 10.1002/pssb.2221500150
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Magnetic Field on the Heat Capacity of CsDy(MoO4)2

Abstract: Recently in some of the rare earth dimolybdates the phase transition into the complicated magnetic ordered state was observed. For example the layered crystals of K D~( M O O~)~ (Tc = 1.1 K) /l/, csDy(M00~)~ (Tc = 1.3 K) /2/, CsGd(Mo04)2 (Tc = 0.45 K) /3/ show this phase transition. This caused a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…This fact corresponds with previous specific heat studies in B = 0 indicating that the system can be described by S = 1/2 Ising model on the square lattice with J/kB = 0.56 K [7]. To estimate magnetic field dependence of CsDy(ΜοO4)2 specific heat, the results of [8] were used where the temperature dependence of specific heat in a constant magnetic field B c was studied.…”
supporting
confidence: 81%
“…This fact corresponds with previous specific heat studies in B = 0 indicating that the system can be described by S = 1/2 Ising model on the square lattice with J/kB = 0.56 K [7]. To estimate magnetic field dependence of CsDy(ΜοO4)2 specific heat, the results of [8] were used where the temperature dependence of specific heat in a constant magnetic field B c was studied.…”
supporting
confidence: 81%
“…4, was obtained using a relation SpB, T q S tot pB 0q ¡ |∆S M pB, T q| [15]. The expressions S tot pB 0q and |∆S M pB, T q| denote the total (lattice and magnetic) entropy, calculated from the experimental specific heat in B 0 T [11,16] and the absolute values of isothermal entropy change in applied external magnetic field, respectively. Applying the procedure depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the crystal symmetry and sufficiently low temperatures, the system approximates an Ising system with the effective spin 1/2 and the easy magnetization corresponding to the crystallographic a axis. Previous specific heat studies performed in zero magnetic field indicated a magnetic phase transition at T c 1.3 K, described within a 2d Ising model [11].…”
Section: Introductionmentioning
confidence: 93%